DETERMINATION OF GEO-INFORMATION CHARACTERISTICS IN THE USER INTERACTION WITH A SYSTEM FOR BETTERMENT TAX CALCULATION - Ramos, Gustavo Dias; Sluter, Claudia Robbi (Boletim de Ciências Geodésicas, 2017)
In this paper, we present some results of research work that seeks to determine how the characteristics of geoinformation should be considered and included in the design of users’ interfaces for a geoinformation system. Through well-known techniques of requirements engineering, we collected and documented the information obtained from potential users of a geoinformation system designed to be used for calculation of betterment taxes. Furthermore, we analyzed the users’ requirements to determine the characteristics of geoinformation in this particular case of tax calculation. We try to define how those geoinformation characteristics can be included in the requirements specification and how to consider them to help designing better geoinformation systems interfaces.